INFLUENCE OF PERIODONTAL STATUS ON PERI-IMPLANT STATUS IN PATIENTS WITH IMPLANT-PROSTHETIC THERAPY - Manole Liviu; Norina Forna; Doriana Agop-Forna; Ioana Mârţu; Cristina Dascălu; Claudiu Topoliceanu; Silvia Mârţu (Romanian Journal of Medical and Dental Education, 2023)
Aim of study. The objective of this study was to evaluate the distribution of implants with peri-implantitis and healthy/peri-mucositis implant sites in relation to the periodontal status of the patients treated with implant-supported fixed prosthetic restorations. Materials and method. The study was performed on 206 implants inserted in a group of 54 patients treated by implant-supported fixed prosthetic restorations. The periodontal and peri-implant status were assessed by clinical and radiological examens. The assessed components of the periodontal status were as follows: periodontal parameters (CAL, PD, MBL), periodontal history, %BOP, %PD ≥ 5mm, stage and progression of periodontal disease, patients’ compliance to supportive periodontal therapy (STP). The distribution of implants without peri-implantitis vs. implants with peri-implantitis was assessed by statistical analyses performed in SPSS 29.0. Results. In patients with periodontal history, it was recorded higher percentage of implants with peri-implantitis (63,2%) vs. implants without peri-implantitis (19%). The distribution of implants in patients with >25% BOP sites was significantly higher for implants with peri-implantitis (52,6%) vs. implants without peri-implantitis (1,2%). The distribution of implants in patients with > 5% PPD ≥ 5mm was significantly higher for implants with peri-implantitis (68,4%) vs. implants without peri-implantitis (23,8%). The distribution of implants in patients with BL/age 1-1,50 was significantly higher for implants with peri-implantitis (57,9%) vs. implants without peri-implantitis (7,1%). The distribution of implants in relation to periodontitis stage/progression IV/C was significantly higher for implants with peri-implantitis (57,9%) vs. implants without peri-implantitis (7,1%). The distribution of implants in relation to periodontitis progression stage C was significantly higher for implants with peri-implantitis (57,9%) vs. implants without peri-implantitis (7,1%). The distribution of implants in relation to non-compliant patients to STP was significantly higher for implants with peri-implantitis (36,8%) vs. implants without peri-implantitis (7,1%). Conclusions. Components of periodontal status (periodontal history, %BOP sites, %PPD ≥ 5mm, BL/age, periodontitis susceptibility, STP compliance patients) influence significantly distribution of implants with peri-implantitis when compared to healthy/peri-mucositis implants.